Znalezisko wczesnośredniowiecznych ozdób z Chodlika, gm. Karczmiska - Miechowicz, Łukasz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
The article presents a late 11th to early 12th-century deposit of early medieval jewellery discovered in December 2023 in Chodlik, Karczmiska municipality. The deposit comprises nine artifacts: three coins, two silver rings, two silver beads forming parts of bag-shaped earrings, a copper temple ring, and a quartz crystal bead. The coins, including the Hungarian denar of Ladislaus I (1077-1095) and two cross denars from the late 11th century, feature suspension holes, suggesting they were likely used as pendants of a necklace. The Orszymowice-type ring and the bag-shaped earrings were crafted using a similar technique involving two silver sheets. Their chemical composition, as well as that of the second ring, a polygonal band, is highly similar, indicating their origin from the same workshop. Such artifacts are rare and belong to the category of elite jewellery. The deposit was discovered in waterlogged meadows on the border between Chodlik, Karczmiska municipality, and Żmijowiska, Wilków municipality, in the vicinity of a probable medieval transport route. The absence of a settlement or burial traces suggests the deposit might have been stored in an organic container that decomposed over time and was subsequently lost. The jewellery could have been a set owned by a single individual. This discovery provides new data on the technological connections and functions of jewellery in the 11th–12th centuries. The deposit is a significant contribution to the study of elite jewellery in early medieval Małopolska.